Long-term survival after chronic subdural haematoma. (December 2016) - Manickam, Appukutty; Marshman, Laurence A.G.; Johnston, Ross
Highlights: Long term survival (LTS) after chronic subdural haematoma (CSDH) is largely unknown. One study reported excess mortality in year 1: actuarial rates occurred thereafter. LTS was markedly less than previously reported: peers lived 12.4 years longer. Although greater in year 1, excess mortality continued through 5-years follow-up. LTS is related to modified Rankin score and co-morbid risk factors. Abstract: Outcome after chronic subdural haematoma (CSDH) is invariably assumed favourable: however, little data regarding long term survival (LTS) exists. One study reported excess mortality restricted to year 1, but with expected actuarial rates thereafter. We aimed to determine LTS after CSDH in a retrospective analysis relative to actuarial data from age-matched controls. Data was obtained in n = 155, (M:F 97:58, 69.3 ± 2.3 years). Follow-up maxima was 14.19 years (mean: 4.02 ± 3.07 years, median: 5.2 years). Mortality in-hospital, at 6 months, 1 year, 2 years and 5 years was n = 13 (8.39%), n = 22 (14.19%), n = 31 (20.35%), n = 42 (27.1%) and n = 54 (34.84%). LTS was significantly worse than controls (5.29 ± 0.59 years vs. 17.74 ± 1.8 years, hazard ratio [HR]: 3.52, P < 0.0001). Death most frequently related to pneumonia/sepsis and ischemic heart disease (IHD). Median modified Rankin score (mRS) in those discharged home (n = 94, 60.65%) was 2 [IQR: 1–3]. Discharge mRS in those who died at 6 months, 1 year, 2 years and 5 years was 5 [IQR: 3–6], 5 [IQR: 4–6], 3 [IQR: 1–3], 4 [IQR: 2–5]. Discharge mRS was significantly worse with year 1 mortality ( P = 0.014). LTS related to discharge mRS (HR: 37.006, P < 0.001), post-operative motor-score (HR: 0.581, P = 0.0026), IHD (HR: 5.186, P = 0.005), warfarin-use (HR: 5.93, P = 0.036) and dementia (HR: 5.39, P = 0.031). No long term recurrences (LTR) were recorded. Although most were discharged home with mRS = 2, LTS was markedly less than previously reported: peers lived 12.4 years longer. Although greater in year 1, excess mortality was not restricted to year 1, but continued throughout prolonged follow-up. LTS related to discharge disability and dependence, and co-morbid risk factors for cerebral atrophy. No LTR suggests that, once ultimately closed, the 'subdural space' remains closed. CSDH patients represent a vulnerable group who require continued long-term medical surveillance.